Agama Khonghucu Sejarah, Ajaran, dan Keorganisasiannya di Pontianak Kalimantan Barat - Sulaiman Sulaiman (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
Current confucius religion research is performed at Pontianak, West KalimantanProvince. The research shows that confucius religion characteristics which are moretraditional come from their ancestor’s tradition. The History reveals the beginningof confucius religion invoking from traditional belief, which is Ru Jiao. The prophetKhong Zi has finalized Ru Jiao into Confucius religion. Confucius followers belief inone God, Prophet, and holybook, and belief in forefather. The history of confuciusreligion ever experienced blur period during new regime administration. However,their leader manage to retain their followers through religious organization.Key words : Khonghucu, history, doctrine, organization